THU0534 NEW CLASSIFICATION CRITERIA FOR RECURRENT AUTOINFLAMMATORY DISEASES APPLIED TO AN INDEPENDENT COHORT: EXPERIENCE FROM THE JIR COHORT DATABASE. (June 2019) - DINGULU, Glory; Georgin-Lavialle, Sophie; Koné-Paut, Isabelle; Pillet, Pascal; Pagnier, Anne; Merlin, Etienne; Kayser, Daniela; Belot, Alexandre; Hofer, Michael; Hentgen, Véronique
Abstract : Background: New classification criteria for the inherited periodic fever syndromes (TRAPS, FMF, MKD and CAPS) have recently been developed during a Consensus Conference held in Genoa in March 2017. Objectives: The aim of our study was to compare these new classification criteria for monogenic recurrent fever syndromes with the diagnoses of clinicians. For this purpose we used the JIRcohort database, an international platform gathering data of patients with pediatric inflammatory disease. Methods: The Genoa classification criteria were applied to all the patients, then compared to the clinical diagnosis of the treating physician. As patient diagnosis could be confirmed or suspected, the patients could have up to two diagnoses. Classification criteria relied on genetical HRF pathogenicity classification. Finally, criteria performance were assessed by firstly determining sensitivity and specificity and secondly analyzing true positive, false positive and false negative patients. Results: 455 patients included to the JIRcohort database with a recurrent fever syndrome were enrolled to the study. CAPS: The analysis of the performance of the CAPS criteria showed sensitivity of 60% and specificity of 98%. 14 patients fulfilled Genoa CAPS classification criteria, with 6 true positive and 8 false positive patients. Patients with confirmatory genotype always fulfilled classification criteria. 4 patients, who carried heterozygous mutations, were false negative. TRAPS: The analysis of the performance of the TRAPS criteria showed sensitivity of 100% and specificity of 98%. 22 patients fulfilled Genoa TRAPS classification criteria, all true positive patients with confirmatory and non-confirmatory genotype. 5 were false negative with 4 patients with non-confirmatory genotype. FMF: The analysis of the performance of the FMF criteria showed sensitivity of 96% and specificity of 89%. 118 patients were true positive while 35 were false positive patients. True positive patients were all patients with confirmatory genotype, patients with non-confirmatory genotype and no mutation. 37 were false positive patients. 5 patients were false negative with 3 patients with non-confirmatory genotype. MKD: The analysis of the performance of the CAPS criteria showed sensitivity of 64% and specificity of 66%. 7 patients with confirmatory genotype were true positive patients. 148 were false positive patients with 44 patients diagnosed TRAPS, FMF, CAPS while the rest were SURF. 4 were false negative including 3 patients with non-confirmatory genotype. Conclusion: This study is the first Genoa criteria evaluation among a cohort of patients seen with recurrent fever. This descriptive study shows tremendous performance Genoa criteria for patients with confirmatory genotype and help classifying patients with non-confirmatory genotype. On the other hand, those classification criteria were less performant when patients did not display at least one gene mutation. Therefore, Genoa classification criteria for TRAPS outperformed the others, because mandatory genetical screening. This study also highlights permissive criteria for clinical CAPS, FMF and MKD. The implementation of biological criteria in MKD would improve MKD criteria. Disclosure of Interests: : Glory DINGULU: None declared, Sophie Georgin-Lavialle Consultant for: novartis, sobi, Speakers bureau: novartis, sobi, Isabelle Koné-Paut Grant/research support from: SOBI has supported drug product (anakinra) for the presented study, Consultant for: SOBI, Novartis, Pfizer, Abbvie, UCB, CHUGAI, ROCHE, Pascal Pillet: None declared, Anne Pagnier: None declared, Etienne Merlin: None declared, Daniela Kayser: None declared, alexandre belot: None declared, Michael Hofer Grant/research support from: Sobi, Consultant for: Novartis, Véronique Hentgen Consultant for: SOBI, Novartis, Abbvie, Speakers bureau: Novartis